Seismic fragility assessment of tall concrete wall structures in Malaysia under far-field earthquakes considering mass irregularity - Fung, Alex Hui Siang (2019)
Over the past decades, Malaysia had encountered far-field and near-field earthquakes. Peninsular Malaysia was constantly affected by the far-fault excitations that originated from the Sumatra earthquakes besides having the earthquakes of local origin while East Malaysia was affected the most by the earthquakes that are occurred in the Southern Philippines despite being surrounded by the local faults. High-rise buildings were more vulnerable to the far-field earthquakes as compared to low-rise buildings. Damages of infrastructures and public buildings due to seismic excitation will cause a huge financial loss to the affected country while endangering the life of people. Thus, a proper retrofitting scheme and an effective disaster risk mitigation plan are required to address the direct seismic risks and the damage resulted from the occurrence of a seismic event. This study specifically delivers the seismic fragility assessment of tall buildings under far-field earthquakes. The main aim of this study is to develop fragility curves of the 2-D structural models undergoing seismic analyses. This study employs pushover analysis and IDA as the chosen non-linear analysis methods in determining the failure mechanism, inter-story demand and capacity as well as developing fragility curves. Two reference buildings with similar building plan and number of stories but with different number of parking levels were selected for seismic evaluation. Five stories were allocated to the parking level of reference building 1 while for reference building 2, it only consists of a three-story parking level in addition to the residential level. The exterior and interior frames of both buildings were selected from grids A and B. A total of 15 ground motion records and a set of 10 incremental PGAs were adopted in the IDA to obtain the drift demand values at each PGA which leaded to the derivation of fragility curves. According to FEMA 356, three performance limit states, namely IO, LS and CP were used in the ETABS software. It was observed that in both buildings, the drift demand values increase with the increase in PGAs. The exterior frames of reference buildings 1 and 2 have a higher range of median drift demand values as compared to the interior frames of similar buildings. In addition, the median drift demand and PGA have a strong correlation with each other in all the four frames analyzed under IDA. On the other hand, reference building 1 provides lower drift capacity values than reference building 2 for both frames. Four fragility curves were developed towards the end of this study, exhibiting the probability of exceeding IO, LS and CP damage states given the range of seismic intensity as the PGA increases from 0.05 g to 0.5 g. The statistical analysis results show that the probability of exceeding IO, LS and CP damage states for the exterior frames is higher than that for the interior frames of both buildings.